Rituximab in multiple sclerosis at general hospital level. (6th February 2020) - Hellgren, Johan; Risedal, Anette; Källén, Kristina
Abstract : Objectives: The use of rituximab (RTX) in multiple sclerosis (MS) is a rapidly increasing choice of disease‐modifying therapy. Efficacy outside specialized university hospital‐based care is not yet systematically investigated. Our aim was to evaluate off‐label RTX treatment for MS at a general hospital in Sweden. Materials and Methods: Subjects with definite MS with at least one rituximab infusion were eligible for inclusion in this retrospective, observational study. Effect was evaluated by monitoring clinical disability, annual relapse rate, new lesions on MRI, and safety by the incidence and severity of adverse events. Results: Among the 83 included subjects, 15 had clinical worsening of disease during the median 23.5 (1‐76) months of follow‐up after RTX initiation: 7/66 with relapsing‐remitting multiple sclerosis (RRMS) and 8/17 with progressive subtypes (PMS). Cumulative survival without worsening was 86% in RRMS and 30% in PMS. The annual relapse rate before RTX vs follow‐up dropped from 0.38 to 0.05 ( P  < .00001). Subjects with new enhancing lesions on MRI during the first year before RTX initiation vs the year after dropped from 0.94 to 0.024 ( P  < .00001) and was only seen in RRMS (1.05‐0.31, P  = .00003). Adverse events were mainly mild. Thirty‐six out of 53 non‐infusion–related adverse events were infections, of which four were serious, including a case of pneumonia with concomitant late‐onset neutropenia. Conclusions: Rituximab was as effective and safe when given at a general hospital outpatient clinic compared with results from previous university hospital‐based studies. Vigilance is required concerning severe adverse events.